Comparative analysis of macronutrient, vitamin, and mineral intake between stunted and non-stunted children in cirebon - Pandanwangi, Siti; Akrom, Akrom; Nurkhasanah, Nurkhasanah; Zuniarto, Ahmad Azrul (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2025)
Background: The food consumed by children greatly affects how they will live in the future. The amount of nutrition that enters a child's body affects their health and intelligence. Macronutrients, vitamins and minerals are vital components in the body for the processes of growth and development, endurance, and other important functions. Low nutritional intake in children will cause them to experience growth failure, resulting in stunting.Objectives: This study was to compare the intake of macronutrients (protein, fat, and carbohydrate), vitamins (A, E, B1, B2, B6, C, folate), and minerals (sodium, potassium, magnesium, calcium, phosphorus, iron, and zinc) between stunted and non-stunted childrenMaterials and Methods: This study used a cross-sectional design. The population of the study was toddlers living in the Tegalwangi area, a sample of 100 children, ages 2 to 5, who were willing to sign a consent form as research subjects was split into 50 stunting and 50 non-stunting children. The time for the study began in January-May 2023. Data was collected using the 3x24 hour nutritional recall questionnaire method, followed by converting nutritional intake through the Nutrisurvey softwareResults: Nutritional intake for stunted children, shows that there are 12 intake criteria below the nutritional adequacy rate, while 5 intake criteria meet the standard. While for children who are not stunted, 12 criteria meet and 5 criteria do not meet the nutritional adequacy standard.Conclusion: Analysis of differences in the intake of the two groups found that there were no significant differences in the intake of macronutrients (carbohydrates), vitamins (E, B2) and minerals (sodium, potassium, calcium and phosphorum) with p>0.05, and significant differences in the intake of macronutrients (protein, fat). vitamins (A, B1, B6, C, folate), and minerals (magnesium, iron, zinc) with p<0.05.